Taxonomic notes on Megalopta Smith, 1853 (Hymenoptera: Halictidae: Augochlorini) with a synopsis of the species in the state of Minas Gerais, Brazil - Santos, Leandro M.; Silveira, Fernando A. (Zootaxa, 2009)
There are twenty-seven described species in the nocturnal bee-genus Megalopta Smith, 1853 (Hymenoptera: Halictidae); of these, 10 were recorded from Brazil but none in the Brazilian state of Minas Gerais. Here, five species of Megalopta are recorded for this state, two of them described as new. Four of these species belong in the subgenus Megalopta Smith s.str.: M. (M.) aegis (Vachal, 1904), M. (M.) amoena (Spinola, 1853), M. (M.) sodalis (Vachal, 1904) and M. (M.) guimaraesi sp.n., and one: M. atlantica sp.n., belongs to the subgenus Noctoraptor Engel, Brooks & Yanega, 1997, which is recorded for the first time for Brazil. A key for the identification of these five species is provided. Based on the examination of the types of species described by H. Friese and J. Vachal, M. ecuadoria Friese, 1926 and M. ochrias (Vachal, 1904) are proposed to be junior synonyms of M. amoena; and M. aethautis (Vachal, 1904) is proposed to be a junior synonym of M. fornix (Vachal, 1904). Lectotypes are designated for M. aeneicollis Friese; 1926, M. armata Friese, 1926; M. boliviensis Friese, 1926; M. cuprea Friese, 1911; and M. sulciventris Friese, 1926. Evidence that Megalopta s.str. is rendered paraphyletic by the recognition of the subgenus Noctoraptor is presented and the potential use of aromatic baits for the inventory of local Megalopta faunas is discussed.